Korelasi Antara Motivasi, Kegiatan, dan Minat Berkunjung Kembali pada Kawasan Agrowisata di Indonesia - Kendran, Ni Made Diah Ayu; Kusuma, Hanson Endra; Riska, Annisa Safira (RUAS, 2023)
Best tourism facilities will be able to compete and be long last time if the planning consider sense of visitor loyalty. A sense of loyalty if related in agro-tourism planning can be interpreted as an intention to revisit and feel comfortable after visitor had a tour. Regarding such a case, this study aimed to find out the correlational relationship between motivation and activity to the intention revisit and feel comfortable in the visited agro-tourism areas. This research used a mixed-method approach (qualitative – quantitative) with data was collected online in an open – ended and close – ended questionnaire. The collected data then analyzed by qualitatively used content analysis and quantitatively used principal component analysis, factor analysis, and multivariate correlation analysis. The results showed that intention to revisit and feel comfortable were influenced by tow factor, there are relaxation as push factor and natural attraction as pull factor